DAMARIS – a flexible and open software platform for NMR spectrometer control - Gädke, Achim; Rosenstihl, Markus; Schmitt, Christopher; Stork, Holger; Nestle, Nikolaus (Diffusion Fundamentals, 2007)
Home-built NMR spectrometers with self-written control software have a long tradition in porous media research. Advantages of such spectrometers are not just lower costs but also more flexibility in developing new experiments (while commercial NMR systems are typically optimized for standard applications such as spectroscopy, imaging or quality control applications). Increasing complexity of computer operating systems, higher expectations with respect to user-friendliness and graphical user interfaces as well as increasing complexity of the NMR experiments themselves have made spectrometer control software development a more complex task than it used to be some years ago. Like that, it becomes more and more complicated for an individual lab to maintain and develop an infrastructure of purely homebuilt NMR systems and software. Possible ways out are: ● commercial NMR hardware with full-blown proprietary software or ● semistandardied home-built equipment and common open-source software environment for spectrometer control. Our present activities in Darmstadt aim at providing a nucleus for the second option: DArmstadt MAgnetic Resonance Instrument Software (DAMARIS) [1]. Based on an ordinary PC, pulse control cards and ADC cards, we have developed an NMR spectrometer control platform that comes at a price tag of about 8000 Euro. The present functionalities of DAMARIS are mainly focused on TD-NMR: the software was successfully used in single-sided NMR [2], pulsed and static field gradient NMR diffusometry [3]. Further work with respect to multipulse/multitriggering experiments in the time domain [4] and solid state NMR spectroscopy multipulse experiments are under development.